Pengembangan Model Blended Learning Berbasis Proyek Untuk Menunjang Kreatifitas Mahasiswa Merancang Pembelajaran Matematika Sekolah Dasar - Wahyudi Wahyudi; Indri Anugraheni; Adi Winanto (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2018)
This research aims to develop a Project-Based Blended Learning (PjB2L) model to support student creativity in designing mathematics learning in elementary school. The method used in this research was R&D with ASSURE development model consisting of six stages: 1) analyze learners, 2) state objectives, 3) select method, media, and materials, 4) utilize media and materials, 5) require learner participation, 6) evaluated and revise. Product validation was done through an expert’s assessment by using the expert’s validation sheet. The practicality of the product is tested with limited trials with college lecturers and some students with questionnaires and interviews. Product effectiveness was seen by implementing limited development testing to a particular class with a one group pretest-posttest design and the result was analyzed by using a Paired-Samples T-Test. The result of this research is a Project-Based Blended Learning (PjB2L) model to support students' creativity in designing mathematics learning plan in elementary school. Validity of the learning model was proven by the result of the expert assessment in learning (face-to-face and on-line), material and instructional media. Effectiveness of the learning model was also proven on the basis of Paired-Samples T-Test of students’ pretest and posttest.